J.-B. Say's 1803 Treatise and the Coordination of Economic Activity - Stefan Hopp (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2004)
Although historians of economic thought emphasize J.-B. Say's contributions to utility theory, the structure of the subject matter of economics, entrepreneur theory and the construction of the "law of markets," they rarely appreciate what Say accomplished in the first edition of the Traité d'Économie Politique. Only in chapters 21 and 22 of his 1803 Treatise, however, does Say sketch business firms as institutions that create and operate markets. In doing so, he essentially provides the basis for a non-walrasian concept of the coordination problem of a decentralized economic system. Thus, concerning Adam Smith's metaphor of the "invisible hand," Say ought to be considered as the first theorist to introduce into economic literature what Robert W. Clower called the "visible fingers" of the "invisible hand."
Keywords: D50; B12; 330; Invisible Hand; General Equilibrium Theory; Jean-Baptiste Say; Market Maker; Say's Law; Des Débouchés; Marktmechanismus; Allgemeines Gleichgewicht; Dogmengeschichte; Theorie; Say Jean Baptiste